Criminalizing the political in a digital age - Bessant, Judith (Critical criminology, 2015)
There is an emergent interest by criminologists in theorising problems that arise when states breach conventional legal norms. This article considers the criminalisation of ‘whistleblowing’ by Manning, Assange and Snowden that revealed illegal actions by the state and major breaches of US and western security intelligence operations. The article asks what such developments mean for the conceptual and normative status of politics and crime constituted in the western liberal frame? It is about criminologists who rely on that paradigm and the need to counter neo-conservative agendas. The article analyzes liberal constitutional democracies with an emphasis on the US. It draws on the work of German theorists Schmitt and Benjamin who stand outside the liberal tradition to highlight how modern states frequently suspends the rule of law and relies on their own sovereign power to declare ‘states of emergency’ to render their own criminal conduct lawful.